2011
DOI: 10.1186/1743-422x-8-466
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HCV genotypes and viral loads in chronic HCV infected patients of Hazara Pakistan

Abstract: Hepatitis C Virus (HCV) genotype and viral load are two significant predictive variables knowledge of which might persuade treatment decisions. The objective of the present study was to identify the distribution of different HCV genotypes circulating in the study area and to estimate viral load in chronically HCV infected patients. Out of total 305 HCV positive patients, 177 (58%) were males and 128 (42%) were females. Frequency breakup of the HCV positive patients was 169, 69, 38 and 29 from Abbottabad, Manse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
26
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
18
26
4
Order By: Relevance
“…This study ascertained that HCV genotypes were spread with equal probability between the both sexes and there was no association between gender and HCV genotypes. These results are in agreement with multiple previous studies indicating little statistical association between genders and genotypes in Pakistan (8,(10)(11)(12). This study contradicts a Libyan study that showed the association of various HCV genotypes with gender (13).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This study ascertained that HCV genotypes were spread with equal probability between the both sexes and there was no association between gender and HCV genotypes. These results are in agreement with multiple previous studies indicating little statistical association between genders and genotypes in Pakistan (8,(10)(11)(12). This study contradicts a Libyan study that showed the association of various HCV genotypes with gender (13).…”
Section: Discussionsupporting
confidence: 94%
“…This study also reported many rare genotypes like 5a, 1c, and 6a, which are uncommon and less reported. Unlike Ali et al (8) sudy findings, the findings of this study support the verdict of some previous studies that showed the presence of genotypes such as 5a, 4a, and 1c in spite of their rare status (9)(10)(11)16). These findings are in contradiction with those of some studies that have shown the partial absence of genotypes 4, 5, and 6 (8,17).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…11,18 A study conducted at Pakistan in 2011 showed a significant higher HCV viral load in genotype 1 as compared to other genotypes. 19 A similar kind of study done in India also showed that viral load in patients with genotype 1 was significantly higher than other HCV genotypes.…”
Section: Discussionmentioning
confidence: 79%